1999
DOI: 10.1095/biolreprod60.2.461
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the Rat Spermatogenic Epithelium Following Androgen Withdrawal: Changes in Apoptosis-Related Genes1

Abstract: Programmed cell death is an important regulatory event in spermatogenesis. However, the molecular events governing apoptosis have not been characterized. Using the Leydig cell-specific toxin ethane dimethanesulfonate (EDS) to withdraw androgen support, we have investigated the relationship between apoptosis and apoptosis-related genes. Adult male Sprague-Dawley rats were injected (i.p.) with 100 mg/kg EDS and killed at times of androgen depletion 2, 5, and 8 days postinjection. A 24-fold increase in the apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(98 citation statements)
references
References 41 publications
4
91
1
2
Order By: Relevance
“…Th e loss of the Insl3 in the testis post-EDS treatment confi rms elimination of the mature Leydig cells, resulting in testosterone depletion to an undetectable level. With the loss of testosterone, there was a signifi cant reduction in the testicular weight and a substantial increase in the germ cell apoptosis, consistent with the previous reports (Morris et al 1997;Taylor et al 1998;Nandi et al 1999;Taylor et al 1999;Woolveridge et al 1999). Although the testosterone replacement had no eff ect on the Insl3 level, the testicular weights and viability of germ cells were maintained at the control levels with replacement of testosterone (EDS+T).…”
Section: Discussionsupporting
confidence: 89%
“…Th e loss of the Insl3 in the testis post-EDS treatment confi rms elimination of the mature Leydig cells, resulting in testosterone depletion to an undetectable level. With the loss of testosterone, there was a signifi cant reduction in the testicular weight and a substantial increase in the germ cell apoptosis, consistent with the previous reports (Morris et al 1997;Taylor et al 1998;Nandi et al 1999;Taylor et al 1999;Woolveridge et al 1999). Although the testosterone replacement had no eff ect on the Insl3 level, the testicular weights and viability of germ cells were maintained at the control levels with replacement of testosterone (EDS+T).…”
Section: Discussionsupporting
confidence: 89%
“…In the last few years, a number of studies have reported the localization of this molecule in Sertoli and/or in germ cells (18,49). The role of this molecule in the physiology of normal testis is also controversial (5, …”
Section: Discussionmentioning
confidence: 99%
“…This interaction occurs in normal physiological conditions and pathological conditions both of which may result in the elimination of germ cells. Among such pathological conditions are toxic exposure (Wine et al, 1997;Boekelheide, 2005), growth factor depletion, hormonal alterations associated with gonadotropin and/or androgen deprivation (Woolveridge et al, 1999;Bakalska et al, 2004), treatment with estradiol (Blanco-Rodr ıguez & Mart ınez-Garc ıa, 1997; Chaki et al, 2006), heat exposure (Yin et al, 1997;Paul et al, 2009), cryptorchidism (Ohta et al, 1996;Mizuno et al, 2009), radiation (Meistrich, 1993;Liu et al, 2007), chemotherapeutic treatment (Cai et al, 1997), and vascular ischemia (Turner et al, 1997(Turner et al, , 2004. Among normal physiological conditions, testicular regression owing to photoperiod (a reversible process) and aging (irreversible process) can be included (Pastor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%